Differentiated kidney tubular cell-derived extracellular vesicles enhance maturation of tubuloids - Rafael Soares Lindoso; Fjodor A. Yousef Yengej; Franziska Voellmy; Maarten Altelaar; Estela Mancheño Juncosa; Theano Tsikari; Carola M. E. Ammerlaan; Bas W. M. Van Balkom; Maarten B. Rookmaaker; Marianne C. Verhaar; Rosalinde Masereeuw (Journal of Nanobiotechnology, 2022)
Abstract The prevalence of end-stage kidney disease (ESKD) is rapidly increasing with the need for regenerative therapies. Adult stem cell derived kidney tubuloids have the potential to functionally mimic the adult kidney tubule, but still lack the expression of important transport proteins needed for waste removal. Here, we investigated the potential of extracellular vesicles (EVs) obtained from matured kidney tubular epithelial cells to modulate in vitro tubuloids functional maturation. We focused on organic anion transporter 1 (OAT1), one of the most important proteins involved in endogenous waste excretion. First, we show that EVs from engineered proximal tubule cells increased the expression of several transcription factors and epithelial transporters, resulting in improved OAT1 transport capacity. Next, a more in-depth proteomic data analysis showed that EVs can trigger various biological pathways, including mesenchymal-to-epithelial transition, which is crucial in the tubular epithelial maturation. Moreover, we demonstrated that the combination of EVs and tubuloid-derived cells can be used as part of a bioartificial kidney to generate a tight polarized epithelial monolayer with formation of dense cilia structures. In conclusion, EVs from kidney tubular epithelial cells can phenotypically improve in vitro tubuloid maturation, thereby enhancing their potential as functional units in regenerative or renal replacement therapies. Graphical Abstract